2018
DOI: 10.1021/acs.macromol.7b02719
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Ferroelectric Behavior in Main-Chain Dipolar Glass Nylons: Cooperative Segmental Motion Induced by High Poling Electric Field

Abstract: Main-chain dipolar glass polymers such as aromatic nylons are promising for high energy density and low loss dielectric applications because of the limited, noncooperative oscillation of highly dipolar amide groups. However, quenched aromatic nylons have been reported to exhibit significant ferroelectric switching upon high field poling. It is desirable to suppress ferroelectric switching for electric energy storage application, and this requires a fundamental understanding of the nature of ferroelectric behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
0
15
1
Order By: Relevance
“…This result indicated that no significant dielectric nonlinearity was observed up to 71.4 MV m À1 . This was different from main-chain dipolar glass polymers reported recently, 37 where significant dielectric loss was observed as a result of high field-induced cooperative segmental motions. The high-field dielectric property was studied by unipolar D-E loop measurements, and discharged U e and efficiency were obtained from the charge and discharge curves (Fig.…”
Section: New Conceptscontrasting
confidence: 99%
See 1 more Smart Citation
“…This result indicated that no significant dielectric nonlinearity was observed up to 71.4 MV m À1 . This was different from main-chain dipolar glass polymers reported recently, 37 where significant dielectric loss was observed as a result of high field-induced cooperative segmental motions. The high-field dielectric property was studied by unipolar D-E loop measurements, and discharged U e and efficiency were obtained from the charge and discharge curves (Fig.…”
Section: New Conceptscontrasting
confidence: 99%
“…The high-field dielectric behavior of SO 2 -PIM was further studied using high voltage BDS (HV-BDS). 37 In Fig. S6 (ESI †), all tan d curves under different electric fields largely overlapped, except for slightly enhanced conduction of impurity ions above 50 1C.…”
Section: New Conceptsmentioning
confidence: 97%
“…12). 170,171 It was found that the presence of the cyano group improves the K from 2.92 of the analogous PI without cyano groups to 3.1-3.5 at room temperature and 1 kHz. In addition, the asymmetric structure of the aromatic diamine monomer can improve the processability and enhance K values of PIs.…”
Section: Dipolar Grafting On Main Chain Of Polar Dielectric Polymersmentioning
confidence: 99%
“…Examples of the main-chain dipolar grafting polymers include but are not limited to aromatic PIs, [167][168][169] PAs, 170 and ArPUs. [171][172][173] The dielectric properties of the main-chain dipolar grafting polymers can be modulated by using different polar chain segments in the polymer backbone, incorporating additional permanent dipoles, varying conjugation length and controlling the degree of crystallinity.…”
Section: Dipolar Grafting On Main Chain Of Polar Dielectric Polymersmentioning
confidence: 99%
See 1 more Smart Citation